Value creation and sport management - Gómez López-Egea, Sandalio (Cambridge University Press, 2010)
"The sports business has become one of the fastest growing industries in recent years. Sports organizations now have the potential to generate massive amounts of revenue through a variety of different channels, including broadcasting rights, advertising and branding. However, the rise of sports-related business has so far received relatively little attention from management scholars and social scientists. This book argues that we can no longer afford to ignore this important economic and social phenomenon. It presents a new conceptual framework based on the concept of value creation to show how we can understand and explain the success and failure of sports organizations. Key concepts are illustrated with case studies of sporting organizations, including Real Madrid, FC Barcelona and the Americas Cup. Written by a team of authors from one of Spain's leading business schools, it provides a unique set of theoretical and practical insights for researchers and sports organization managers"--